Central nervous system compartmentalization of HIV-1 subtype C variants early and late in infection in young children. - Christa Buckheit Sturdevant; Anna Dow; Cassandra B Jabara; Sarah B Joseph; Gretja Schnell; Nobutoki Takamune; Macpherson Mallewa; Robert S Heyderman; Annelies Van Rie; Ronald Swanstrom (PLoS Pathogens, 2012)
HIV-1 subtype B replication in the CNS can occur in CD4+ T cells or macrophages/microglia in adults. However, little is known about CNS infection in children or the ability of subtype C HIV-1 to evolve macrophage-tropic variants. In this study, we examined HIV-1 variants in ART-naïve children aged three years or younger to determine viral genotypes and phenotypes associated with HIV-1 subtype C pediatric CNS infection. We examined HIV-1 subtype C populations in blood and CSF of 43 Malawian children with neurodevelopmental delay or acute neurological symptoms. Using single genome amplification (SGA) and phylogenetic analysis of the full-length env gene, we defined four states: equilibrated virus in blood and CSF (n = 20, 47%), intermediate compartmentalization (n = 11, 25%), and two distinct types of compartmentalized CSF virus (n = 12, 28%). Older age and a higher CSF/blood viral load ratio were associated with compartmentalization, consistent with independent replication in the CNS. Cell tropism was assessed using pseudotyped reporter viruses to enter a cell line on which CD4 and CCR5 receptor expression can be differentially induced. In a subset of compartmentalized cases (n = 2, 17%), the CNS virus was able to infect cells with low CD4 surface expression, a hallmark of macrophage-tropic viruses, and intermediate compartmentalization early was associated with an intermediate CD4 entry phenotype. Transmission of multiple variants was observed for 5 children; in several cases, one variant was sequestered within the CNS, consistent with early stochastic colonization of the CNS by virus. Thus we hypothesize two pathways to compartmentalization: early stochastic sequestration in the CNS of one of multiple variants transmitted from mother to child, and emergence of compartmentalized variants later in infection, on average at age 13.5 months, and becoming fully apparent in the CSF by age 18 months. Overall, compartmentalized viral replication in the CNS occurred in half of children by year three.